MANAJEMEN LABA DAN REPUTASI AUDITOR - Yossi Diantimala (Jurnal Telaah dan Riset Akuntansi, 2010)
This paper is aimed to examine the difference of earnings management between firms audited by Big Four Auditor and firms audited by non-Big Four Auditor. Sample is randomly selected of non-financial firm listed at Indonesia Stock Exchange period 2009.  Earnings management is measured by working capital accruals. Auditor reputation is measured by dummy variable Big Four Auditors and Non-Big Four Auditors. Hypothesis test is done by applying Independen Sample T-Test. The result shows that mean of accruals of firms audited by Big Four Auditor is higher than mean of accruals of firms audited by Non-Big Four Auditor. But, the accruals not statistically significant.      Keywords: earnings management, auditor reputation, Big Four versus Non-Big Four Auditors.